Dictators' endgames - Croissant, Aurel; Eschenauer-Engler, Tanja; Kühn, David (Oxford scholarship online Political Science, 2024)
'Dictators' Endgames' examines the political role of the military in 'dictators' endgames': large-scale nonviolent mass protests in autocracies that demand the regime leader's removal from office. It addresses the question why some militaries defend an embattled autocrat by violently cracking down on the protestors, whereas others side with the opposition or decide to stage a coup d'état. The book introduces a systematic definition and operationalisation of the 'dictator's endgame' as a situation of non-violent mass mobilisation, in which the dictator's political survival depends on the loyalty of the military leaders.